(untitled) (Simbiótica. Revista Eletrônica, 2024)
This article, based on the Durkheimian theoretical framework, discusses how recent educational transformations, implemented by the High School reform (Law nº 13,415/2017), impact the role of the school and guides the training of students towards individualism consistent with the principles of neoliberal rationality. In this sense, the work is divided into three parts. The first focuses on presenting the reform of High School and its articulation with neoliberal governmentality and the formation of the individual for the “new” spirit of capitalism. The second, how education and school are discussed in Durkheim’s sociology, from the works Education and Sociology, Moral Education and Pedagogical Evolution. Finally, in the third stage, we seek to relate the republican education defended by Durkheim and his criticism of the notion of “sordid” individualism of a utilitarian nature, which we can see its nuances in the reform that is underway in Brazilian High School.